2011
DOI: 10.1177/0884533611405993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Lifestyle Modification Program for Treatment of Overweight and Nonmorbid Obesity in Primary Healthcare and Its Influence on Health‐Related Quality of Life

Abstract: An LMP focused on balanced and moderate energy-restricted diets, increased physical activity, and psychological support may improve the anthropometric parameters and the quality of life in moderately obese patients treated in a primary healthcare center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
2
11
0
2
Order By: Relevance
“…However, the percentage of energy supplied by carbohydrate did not increase enough to attain the goal set out. Similar findings have been reported in other interventional studies in which the dietary recommendations were based on the same criteria (2,22). However, different studies suggest that diets supplying 40 -50% of total energy from carbohydrate may be effective alternatives to those insisting on Ͼ50% of energy coming from this macronutrient, since similar weight losses were achieved (14,28,38).…”
Section: Discussionsupporting
confidence: 86%
“…However, the percentage of energy supplied by carbohydrate did not increase enough to attain the goal set out. Similar findings have been reported in other interventional studies in which the dietary recommendations were based on the same criteria (2,22). However, different studies suggest that diets supplying 40 -50% of total energy from carbohydrate may be effective alternatives to those insisting on Ͼ50% of energy coming from this macronutrient, since similar weight losses were achieved (14,28,38).…”
Section: Discussionsupporting
confidence: 86%
“…Fontaine and Barofsky [42] emphasized that health-related quality of life evaluations may help obese individuals redefining treatment goals beyond weight loss and this may help shifting the focus from simple weight reduction to a behavioral change resulting in a healthier lifestyle. In our study, the SF-36 scale revealed a significant increase in PCS and MCS, which was in accordance with the results of similar studies [42,43,44,45,46]. These results support the hypothesis that interventions focusing on lifestyle changes may be effective in overweight and obese women in improving quality of life, especially in physical and mental function fields.…”
Section: Discussionsupporting
confidence: 82%
“…2 Significant difference from non-Hispanic White. 3 Significant difference from women. 4 Significant difference from Hispanic.…”
Section: Introductionmentioning
confidence: 99%